Lycium barbarum polysaccharide reverses drug resistance in oxaliplatin-resistant colon cancer cells by inhibiting PI3K/AKT-dependent phosphomannose isomerase - Ma, Lijun; Ai, Fangfang; Xiao, Hongyan; Wang, Fang; Shi, Lei; Bai, Xuehong; Zhu, Yongzhao; Ma, Wenping (Frontiers in Pharmacology, 2024)
We aimed to explore the effect of LBP in combination with Oxaliplatin (OXA) on reversing drug resistance in colon cancer cells through in vitro and in vivo experiments. We also aimed to explore the possible mechanism underlying this effect. Finally, we aimed to determine potential targets of Lycium barbarum polysaccharide (LBP) in colon cancer (CC) through network pharmacology and molecular docking.